O Banco do Brasil como banco público e banco comercial: mudança e continuidade no governo Lula (2003-2010) - Lucchesi, Alexandre Fávaro (2012)
The main objective is to investigate the movements of change and continuity in Bank Of Brazil (BB) policies through the period of Lula government (2003-2010), based on a comparison of this period and the one correspondent to president Fernando Henrique Cardoso (1995-2002). It is also in focus to purpose and evaluate statistics of the BB as a joint capital company, what demands to analyze its capability to respond both to the controlling shareholder (the National Treasure, once it is a state owned bank) and the commercial bank logic that is, to achieve financial profits. In addition, this work discusses the role of BB during the international credit crises and attempts to offer elements for a better analysis of Lula government. Therefore literature with discussions about state owned banks is reviewed. In addition, it is provided data research of Brazilian financial system, BB and Brazilian private banks as big as BB. The general conclusion is that the BB is presenting an increasingly commercial aspect, although the bank remains an important instrument of government policies and has presented a central performance during the crises